Adar3 Is Involved in Learning and Memory in Mice - Mladenova, Dessislava; Barry, Guy; Konen, Lyndsey M.; Pineda, Sandy S.; Guennewig, Boris; Avesson, Lotta; Zinn, Raphael; Schonrock, Nicole; Bitar, Maina; Jonkhout, Nicky; Crumlish, Lauren; Kaczorowski, Dominik C.; et al. (Frontiers in Neuroscience, 2018)
The amount of regulatory RNA encoded in the genome and the extent of RNA editing by the post-transcriptional deamination of adenosine to inosine (A-I) have increased with developmental complexity and may be an important factor in the cognitive evolution of animals. The newest member of the A-I editing family of ADAR proteins, the vertebrate-specific ADAR3, is highly expressed in the brain, but its functional significance is unknown. In vitro studies have suggested that ADAR3 acts as a negative regulator of A-I RNA editing but the scope and underlying mechanisms are also unknown. Meta-analysis of published data indicates that mouse Adar3 expression is highest in the hippocampus, thalamus, amygdala and olfactory region. Consistent with this, we show that mice lacking exon 3 of Adar3 (which encodes two double stranded RNA binding domains) have increased levels of anxiety and deficits in hippocampus-dependent short- and long-term memory formation. RNA sequencing revealed a dysregulation of genes involved in synaptic function in the hippocampi of Adar3-deficient mice. We also show that ADAR3 transiently translocates from the cytoplasm to the nucleus upon KCl-mediated activation in SH-SY5Y cells. These results indicate that ADAR3 contributes to cognitive processes in mammals.